Why are people with high self-control happier? The effect of trait self-control on happiness as mediated by regulatory focus - Cheung, Tracy T. L.; Gillebaart, Marleen; Kroese, Floor; De Ridder, Denise (Frontiers in Psychology, 2014)
Background: While self-control has often been related to positive outcomes in life such as higher academic achievements and better health, recent insights reveal that people with high trait self-control (TSC) may even experience greater life satisfaction or happiness. Objective: The current study further scrutinizes this potential association between TSC and happiness, and examines how regulatory focus, which is the way people frame and direct their goal pursuit strategies, plays a role in this relationship. Accordingly, the present study examines the mediating role of regulatory-focus (promotion and prevention focus) on the relationship between TSC and happiness. Method: Data was collected from 545 individuals (65.9% female, Mage = 27.52 years) regarding their TSC, regulatory focus, and happiness. Results: Mediation analyses demonstrate that TSC positively predicts happiness, while this effect was partially mediated by relatively more promotion focus and less prevention focus. Conclusion: Such findings suggest that people with higher TSC are happier possibly because they are: (1) more promotion-focused on acquiring positive gains thereby facilitating more approach-oriented behaviours, and (2) less prevention-focused on avoiding losses thereby reducing avoidance-oriented behaviours. These findings are relevant for topical scientific debates regarding the underlying mechanisms of self-control regarding initiatory and inhibitory behaviours.